Gömbös Gyula 1934-es varsói látogatása a lengyel politikai sajtó és diplomáciai dokumentumok tükrében - Debreceni, Péter (Közép-Európai Közlemények, 2016)
The first news of the visit of the Hungarian Prime Minister, Gyula Gömbös surfaced in spring of 1934. They received the most publicity in the press of the neighbouring countries, but they also caused some discomfort in Rome. His arrival was planned for the 15th of October, postponed a few day – as he attended the funeral of the Yugoslavian king – but the actual reception of Gömbös was more than a gesture of sympathy from the Poles towards the Hungarians, whom found themselves in the center of attacks of international press. The Hungarian Prime Minister arrived to Warsaw on the 19th of October, where he met leading Polish politicians, along with Marshall Piłsudski. Aside the official events and friendly reception – just as the Polish political interest dictated – not a lot of information leaked about the actual negotiations. Apart from keeping the international press in the dark, these discussions had concrete effect on the intellectual and economic level and paved the road to government level meetings between Hungarians and Poles, which has climaxed in the five day visit of Miklós Horthy and Kálmán Kánya in the February of 1938.